Fisika Kebahagiaan : Relativitas Sains dan Pendidikan Islam - Robingun Suyud El Syam; Ahmad Khoiri (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
This article attempts to reveal the physics of happiness in relation to the field of Islamic education, starting from the relativity of religion and science. This research is a literature review with a qualitative descriptive approach. The research findings conclude: through the physical laws of electric current and Ohm's law, it is known that the value of gratitude is like the strength of the electric charge in the light of a lantern. The brightness of the headlights depends on the strength of the electric current. Happiness really depends on the quality of a person being grateful for the blessings they receive. If so, the physics of happiness is a person's ability to be grateful to others, and feel grateful to Allah for whatever blessings have been bestowed upon him. From here, Islamic education must prioritize students so that they get used to being grateful in their daily lives. These results offer implications for living life and highlight the importance of moral improvement for grateful people to understand the realities of their lives. We discuss promising directions for future research with cross-disciplinary implications, towards nondichotomous Islamic education.